Hybrid Imaging Techniques in the Diagnosis of Ventricular Myocardial Inflammatory Processes in Patients with Atrial Fibrillation of Unknown Etiology - Yu. N. Il’yushenkova; S. I. Sazonova; R. E. Batalov (Вестник рентгенологии и радиологии, 2019)
Atrial fibrillation is the most common type of cardiac arrhythmia. Identification of an etiological factor for the occurrence and maintenance of atrial fibrillation is of paramount clinical importance and is a necessary condition for successful treatment.The paper describes a clinical case of myocarditis diagnosed in a patient with atrial fibrillation resistant to drug therapy. Additionally, the patient underwent single-photon emission computed tomography/computed tomography with 99mTc-pyrophosphate to diagnose a myocardial inflammatory process, followed by comparison of results and histological findings.